2021
DOI: 10.1039/d0gc03478a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a fully biobased cellulose-3-(2-hydroxyphenyl) propionate ester with antioxidant activity and UV-resistant properties by the DBU/CO2/DMSO solvent system

Abstract: A novel fully biobased cellulose-3-(2-hydroxyphenyl) propionate ester with satisfactory antioxidant activity and UV-resistant properties was first prepared using cellulose and 3,4-dihydrocoumarin (DHC) in a DMSO/DBU/CO2 solvent system without adding any external catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 68 publications
3
15
0
Order By: Relevance
“…The melting flow temperatures (both T fi and T fi ) of the thermoplastic SCEs almost decreased with the DS v values increasing (Figure e), and the minimum T fi and T fc of SCEs (related to 500R-4H-9) were 114 and 152 °C, respectively (Table S3). This phenomenon was ascribed to the decrystallization and plastification by stearoyl groups (Figure f), which was in line with our previous work and the homogenous strategies reported by other researchers. Furthermore, thermal gravimetric analysis (TGA) was conducted to evaluate the thermal stability and to give practical melt-processing windows (the temperature gap between T fi and initial degradation temperature) of SCEs. According to TGA results (Figure S18 and Table S3), the prepared thermoplastic SCEs with DS v beyond 1.62 showed wide melt-processing windows of 102–153 °C, providing practical feasibility for their thermal processing.…”
Section: Resultssupporting
confidence: 86%
“…The melting flow temperatures (both T fi and T fi ) of the thermoplastic SCEs almost decreased with the DS v values increasing (Figure e), and the minimum T fi and T fc of SCEs (related to 500R-4H-9) were 114 and 152 °C, respectively (Table S3). This phenomenon was ascribed to the decrystallization and plastification by stearoyl groups (Figure f), which was in line with our previous work and the homogenous strategies reported by other researchers. Furthermore, thermal gravimetric analysis (TGA) was conducted to evaluate the thermal stability and to give practical melt-processing windows (the temperature gap between T fi and initial degradation temperature) of SCEs. According to TGA results (Figure S18 and Table S3), the prepared thermoplastic SCEs with DS v beyond 1.62 showed wide melt-processing windows of 102–153 °C, providing practical feasibility for their thermal processing.…”
Section: Resultssupporting
confidence: 86%
“…EHL- g -P(DHC- alt -SO) was dissolved in DMF with various concentrations, and the antioxidant properties were appraised according to the well-established DPPH-based colorimetric protocol under different conditions. 43 LD5S5-3 (5 mg mL −1 ) showed excellent free-radical scavenging ability, reaching 90% scavenging activity within 20 min, as presented by a color change from purple to pale yellow in a flash (Fig. 8A and F).…”
Section: Resultsmentioning
confidence: 99%
“…DBU has been identified as an effective organocatalyst for transesterification reactions, 53,54 and even the ROP of cellulose with DHC to form cellulose-3-(2-hydroxyphenyl)propionate ester. 43 To our delight, EHL initiated the ROAP of DHC and epoxides and it proceeded successfully under the designed conditions in this study, and the results are shown in Table 1. The molar ratio of DHC, epoxides and DBU can be quantitatively used according to the whole hydroxyl group content in EHL, which can be evaluated by 31 P NMR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations